On the polynomial approximation of solution for the Cauchy problem - Ismailov , Z. I. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
The Cauchy problem for a nonhomogeneous first-order differential-operator equation of parabolic type in a Hilbert space is considered. Polynomial approximations and estimates of their convergence are obtained which depend on the character of the right-hand side and the initial conditions.